2005
DOI: 10.1161/01.cir.0000157146.86758.bc
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Eplerenone Compared With Placebo in Patients With Myocardial Infarction Complicated by Left Ventricular Dysfunction and Heart Failure

Abstract: Background-In the Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHE-SUS), aldosterone blockade with eplerenone decreased mortality in patients with left ventricular systolic dysfunction and heart failure after acute myocardial infarction. The present study was performed to evaluate the cost-effectiveness of eplerenone compared with placebo in these patients. Methods and Results-A total of 6632 patients with left ventricular systolic dysfunction and heart failure after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 26 publications
(23 reference statements)
1
37
0
4
Order By: Relevance
“…17 Briefly, costs from all participating countries were determined by quantifying resource use, applying the US Medicare Fee Schedule, and standardizing costs to US dollars for the year 2001. For inpatient hospitalizations during follow-up, an investigator blinded to patient characteristics and treatment group assigned diagnosis-related groups to each hospitalization.…”
Section: Cost Assessmentmentioning
confidence: 99%
“…17 Briefly, costs from all participating countries were determined by quantifying resource use, applying the US Medicare Fee Schedule, and standardizing costs to US dollars for the year 2001. For inpatient hospitalizations during follow-up, an investigator blinded to patient characteristics and treatment group assigned diagnosis-related groups to each hospitalization.…”
Section: Cost Assessmentmentioning
confidence: 99%
“…More recently, the Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS) showed that adding a selective MR antagonist, eplerenone, to optimal medical therapy reduces morbidity and mortality among patients with acute myocardial infarction complicated by left ventricular dysfunction and heart failure (6). Based on the results from these two multicenter clinical analyses and other clinical studies (7,8), most national guideline groups now recommended MR antagonists in preference to other antihypertensive agents in hypertensive patients with heart diseases (9 -11). However, recent studies have also indicated the potential roles of aldosterone and MR in the pathogenesis of renal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Several cost of illness and cost of care analyses suggest that HF poses a great economic burden to health care providers and society as a whole [8]. HF is the single most frequent cause of hospitalization for people aged 65 and older.…”
Section: Introductionmentioning
confidence: 99%
“…If the same cost-effectiveness endpoints are used (e.g., costs per life-year saved), it is possible to compare treatments across various indications. Although a US economic evaluation of the EPHESUS trial has become available recently [8], it is still required by national Swiss policy makers to obtain cost-effectiveness estimates adapted to the particular situation in Switzerland.…”
Section: Introductionmentioning
confidence: 99%